PHYSICIAN KNOWLEDGE AND RESPONSIBILITY OF PRESCRIPTION POLICY - Isna Rahmawati; Venia Ilma Dwi Prastika (Universitas Airlangga, 2020)
Background: The minimum standard of generic prescription drugs at a hospital is at 90%. However, the preliminary study discovered the use of generic drugs at Kalisat District Hospital, Jember from 2009 to 2011 was amounted to 57.50%, while the use of patent medicines was at 42.50%. This difference indicates unachieved standard of generic prescription drugs at the Hospital. Aims: This study identified doctors’ knowledge and responsibility of drug prescription policy at Kalisat District Hospital.Methods: This descriptive and observational study employed a cross-sectional design. The data were collected randomly from 50 prescription documents of Kalisat District Hospital, Jember from April to July 2013. This study involved 6 general practitioners, 2 dentists, and 4 specialists. Results: There was a strong correlation between doctors’ specialization and responsibility for pescribing generic drugs. Doctors’ knowledge about prescription policy of generic drugs was still lacking at 58.3%, while doctors’ responsibility for prescribing generic drugs was satisfying. Conclusion: Doctors at Kalisat District Hospital have an excellent sense of responsibility in prescribing generic drugs even though they have insufficient knowledge. The Hospital should conduct trainings, provide incentives, improve policies, monitor and evaluate generic prescriptions. Keywords: generic drugs, prescription, doctors’ responsibility, doctors’ knowledge.